Analisa Perbandingan Uji Performa Pelumas Sintetik dan Pelumas Mineral Pada Aplikasi Sepeda Motor Honda Vario 150 - Maulana, Iqmal; Suardi, Suardi; Abdillah, Tomi (Rekayasa Material, Manufaktur dan Energi, 2026)
Lubricants play a crucial role in every component of an automotive engine, including motorcycles. Without lubricants, the engine cannot function properly. Lubrication reduces friction between components such as piston rings and linear bearings, cools the engine (coolant), prevents wear, and protects against corrosion. Lubricant additive technology can even remove contaminants from fuel combustion, keeping the engine clean and efficient. Synthetic lubricants are made from chemically processed hydrocarbons, resulting in superior formulas compared to mineral lubricants, with a balanced formula structure, lower SAE viscosity grade, optimal oxidation resistance, and performance, as well as detergent and metal-protecting additives. Numerous performance tests of mineral and synthetic lubricants have been conducted, but these are limited to lubricant performance. Further testing is needed, including lubricant lifespan, solid contaminant content, and the cleanliness of engine components from deposits. This study conducted a road test on two samples of mineral lubricant and synthetic lubricant for automatic motorcycles, SAE 10W-30 API Service SL JASO MA. This test was applied to a Honda Vario 150 motorcycle used by an online motorcycle taxi driver who worked an average of 8 hours daily for 3 months. The lubricant was changed monthly, prior to laboratory testing, known as Used Oil Analysis (UOA). The test results demonstrated that the Shell Advance 10W-40 synthetic lubricant performed superiorly compared to the Federal 10W-30 mineral lubricant, with stable viscosity and total base number parameters, minimal particle contamination, and optimal engine component condition.